STRATEGI PENGELOLAAN MODEL PENDIDIKAN INKLUSIF SEBAGAI SEKOLAH RAMAH ANAK BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS - Pauji, Ade Ikbal (Manajerial | Journal Manajemen pendidikan islam, 2024)
Strategic management provides an appropriate for determining the direction of successful development of educational institutions. Implementing an inclusive education model can provide broad access for children with special needs to receive educational services. In general, several problems that often arise in the implementation of inclusive education models are lack of school readiness, managerially and administratively in managing and providing appropriate services for children with special needs. The aim of this research is to explain the implementation of strategic management in determining appropriate strategies to make inclusive schools child-friendly for students with special needs in regular classes. The approach used is descriptive qualitative. Data collection techniques use in-depth interview techniques, in-depth observation and documentation. The research results show that a child-friendly inclusive education model can be implemented through several strategies, management of new students, management of teaching staff, management of disability-friendly infrastructure, as well as curriculum development by designing special coaching programs for students with special needs.